Can Legal Professionals Distinguish between Group-level and Individual-level Expert Testimony? - Donner, Rosa (fi=Turun yliopisto|en=University of Turku|, 2018)
The G2i (group to individual) challenge refers to the problematic application of scientific knowledge based on group-level data to a particular legal case. The G2i challenge is present every time an expert witness provides evidence in court. We investigated Finnish legal professionals’ and law students’ sensitivity to the G2i challenge. We did this using a vignette study format, in which four different cases were presented together with different types of evidence and presented by either experienced or inexperienced experts. Participants provided their perceived probability of guilt before and after evidence was presented. After evidence, they also provided an estimate of the sufficiency of the evidence. Our results showed that neither legal professionals nor law students were sensitive to the G2i challenge and did not distinguish between different levels of evidence. Contrary to previous studies, we did not observe over-reliance among legal professionals on experience and credentials of expert witnesses.